The effects of Kangxianling on renal fibrosis as assessed with a customized gene chip - 董飞侠 张新志 吴峰 何立群 (Journal of traditional Chinese medicine, 2012)
OBJECTIVE：To determine the mechanisms by which Kangxianling（KXL） treats renal interstitial fibrosis using a customized gene chip.METHODS：Twelve out of 18 specific pathogen-free sprague dawley（SPF SD） rats underwent a unilateral ureteral occlusion.These rats were then randomly assigned into either the model unilateral ureteral obstruction（UUO） or Kangxianling（KXL） group.The other six rats were assigned to the sham-operated group.The UUO and sham-operated groups were given normal saline via intragastric administration,whereas the KXL group was given KXL via intragastric administration.All rats were sacrificed for renal tissue collection（i.e.left nephridial tissue）,and the detection of genetic changes with the customized chip.RESULTS：Compared to the sham-operated group,transforming growth factor-β1（TGF-β1）,Smad2,and Smad3 genes were significantly up-regulated in the UUO group,with 〉1.5-fold rise（P〈0.01）.The Smad7 gene was significantly reduced in the UUO versus sham-operated group,with a down-regulation of 〉1.5-fold（P〈0.01）.In the KXL group,TGF-β1,Smad2,and Smad3 genes were significantly reduced compared to the UUO group,with a down-regulation of 〉1.5-fold（P〈0.01）,whereas the Smad7 gene was significantly increased compared to the UUO group,with an up-regulation of 〉1.5-fold（P〈0.01）.CONCLUSION：It was found that KXL can significantly reduce the gene levels of TGF-β1,Smad2,and Smad3.Immunohistochemistry findings also revealed significantly lower TGF-β1/Smads-mediated gene transcription activity.These findings suggest that KXL may negatively regulate the TGF-β1/Smads signal pathway to inhibit the occurrence of renal fibrosis.